Pengaruh Dana Pihak Ketiga, Inflasi, Modal Bank, dan Suku Bunga Dasar Kredit terhadap Penyaluran Kredit - Eklesia, Maria Indah; Riyadi, Selamet (Jurnal Ilmu Manajemen, 2021)
The purpose of this research to analyze the effect of third party fund, inflation, bank capital and prime lending rate on the distribution of credit. The samples use in this research are four stated-owned enteprises bank listed on the Indonesia Stock Exchange period 2015-2019. The four banks are: Bank Rakyat Indonesia Tbk, Mandiri Bank Tbk, Bank Negara Indonesia Tbk, Bank Tabungan Negara Tbk. The sample selection use purposive sampling method. The data obtained from the quarterly financial statement of each bank period 2015-2019. The analysis technique for hypothesis testing is panel data regression, which is processed by Eviews 10.0. The result obtained   that simultaneously third party funds, inflation, bank capital and prime lending rate had an effect and were feasible to explain lending. Partially, the variables of third party funds and bank capital have a significant positive effect on lending, while the inflation variable does not have a significant effect on lending, and the prime lending rate variable has a negative effect on lending.